Recycling wastes to mitigate trace elements contamination in plants: a new horizon for urban agriculture in polluted soils - Barbillon, Anne; Lerch, Thomas Z.; Araujo, José H. R.; Manouchehri, Nastaran; Robain, Henri; Pando-Bahuon, Anne; Cambier, Philippe; Nold, François; Besançon, Stéphane; Aubry, Christine (Frontiers in Soil Science, 2023)
Urban agriculture development often faces the problem of soil pollution. Soil engineering consisting in the addition over polluted soils of a top layer made of recycled wastes is a promising solution. This study was co-constructed with urban farmers and aimed at testing in situ the feasibility of growing vegetables safe for consumption in substrates consisting of organic and inorganic waste, directly overlaying soil polluted by trace elements (TE). Two plants were tested: radishes and tomatoes. Three substrates were tested: 1) sheep manure mixed with composted ramial chipped wood (SHW); 2) biowaste compost mixed with mushroom compost and ramial chipped wood (BMW); and 3) deep excavated subsoils mixed with green waste compost (EXC). Only radishes grown in EXC presented levels of TE below the threshold values. For all the other cases, cadmium levels were above the threshold values. This result concerning plant contamination by TE is consistent with a contamination of SHW and BMW substrates by the polluted soil underneath. EXC contained lower TE content, suggesting that mineral materials limited the transfer from the polluted soil towards the substrate overlay. We concluded that adding a combination of mineral and organic waste on top of polluted soils may better mitigate vegetables contamination than adding only organic waste. However, this result was not observed for all tested vegetables. More research is needed to evaluate the best substrate candidate and its adequate thickness, to study its physico-chemical evolution over a longer period of time and to test a larger panel of vegetables.